Three-dimensional golf clubhead-ball impact models for drivers and irons - Caldwell, A.; McPhee, J. (Sports Engineering, 2024)
Impact models are an important tool for golf equipment design as they allow for computer simulations to evaluate and optimize performance. There are several published driver impact models for this purpose. However, existing impact models have no or limited experimental validation to support their conclusions. The aim of this research was to extend several impact models from the literature to predict three-dimensional driver impacts and, for the first time, iron impacts. The accuracy of these models was evaluated using experimental data. Two impulse-momentum and three continuous contact models were applied to create dynamic models to predict driver and iron golf shots. While finite element models are used to design golf clubs, they were not considered here due to their high computational requirements. For modeling driver impacts, an adjusted IM model was the most accurate at predicting ball launch conditions. Ball speed was the most accurate launch condition with a mean absolute error of 1%. The error for vertical launch angle and backspin was less than 10%. However, the error for sidespin and horizontal launch angle (azimuth) was between 30 and 50%. For modeling 7-iron shots, a two-layer ball with a volumetric normal force model was the most accurate of the models considered. The experimental error for ball speed was 2%. The remaining errors were similar to the driver model.